To solve the equation \(-5(3x - 3) + 4x - 5 = -12\), we will first simplify the left-hand side.
-
Distribute \(-5\) across \((3x - 3)\): \[ -5(3x) + (-5)(-3) = -15x + 15 \] So the equation becomes: \[ -15x + 15 + 4x - 5 = -12 \]
-
Combine like terms: \[ -15x + 4x + 15 - 5 = -12 \] This simplifies to: \[ -11x + 10 = -12 \]
-
Next, isolate the term with \(x\) by subtracting 10 from both sides: \[ -11x = -12 - 10 \] Thus, \[ -11x = -22 \]
-
Now, divide both sides by \(-11\): \[ x = \frac{-22}{-11} = 2 \]
So, the solution to the equation is: \[ \boxed{2} \]